2019
DOI: 10.5606/ehc.2019.66344
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adult isolated ulnar diaphyseal fractures: A comparison of new-generation locked intramedullary nail and plate fixation

Abstract: Objectives: This study aims to compare the radiological and functional results of adult patients with isolated ulnar diaphyseal fractures treated with plate and new-generation locked intramedullary nail (IMN). Patients and methods: The study included 57 patients (38 males, 19 females; mean age 39.1 years; range, 18 to 77 years) with isolated ulnar diaphyseal fractures treated with IMN or plate fixation between January 2008 and December 2017. Thirty patients (Plate group) were treated with plate fixation and 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In previous studies on adult forearm fractures, the fluoroscopy time in patients who underwent IMN (1.2-7 minutes) was significantly longer than that in patients who were treated with plate osteosynthesis (0-2 minutes). 14 , 17 , 18 , 35 , 37 , 38 In our study, which is consistent with the literature, fluoroscopy time was significantly longer in patients who underwent IMN (21.3 seconds) than in patients who underwent plate osteosynthesis (2.7 seconds). The long fluoroscopy time was the major disadvantage of using IMNs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In previous studies on adult forearm fractures, the fluoroscopy time in patients who underwent IMN (1.2-7 minutes) was significantly longer than that in patients who were treated with plate osteosynthesis (0-2 minutes). 14 , 17 , 18 , 35 , 37 , 38 In our study, which is consistent with the literature, fluoroscopy time was significantly longer in patients who underwent IMN (21.3 seconds) than in patients who underwent plate osteosynthesis (2.7 seconds). The long fluoroscopy time was the major disadvantage of using IMNs.…”
Section: Discussionsupporting
confidence: 91%
“…When the studies in the literature were examined, it was found that the operative time in patients with forearm fractures was shorter in the patient groups in which IMN (range, 43-61 minutes) was applied than in the patient groups in which osteosynthesis with the plate (range, 63-74 minutes) was used. 17 , 18 , 35 , 37 Patients in the IMN group had a much shorter operative time (69.7 [range, 45-110] minutes) than patients in the plate group (88.2 [range, 50-130] minutes) in our study. As the incisions were small and the procedure was simple, the surgery required less time.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…An important study reporting the results of surgery using the same nail design was conducted by Kibar and Kurtulmuş. [ 17 ] In their study, the mean follow-up time was 29.8±13.2 months in the plate group and 21.6±7.6 months in the IMN group. It was reported that implant removal was not performed due to irritation in any of the patients who underwent nailing during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a recent study compared locking IMN with plate-screw fixation in isolated fractures of the distal third of the ulna diaphysis and, according to the Grace-Eversmann score, similar and satisfactory results were obtained in both groups: excellent/good results in 76% of the IMN group and in 86% of the plate group. [ 17 ] The time to union was reported to be a mean of 12 weeks in the IMN group and 13 weeks in the plate group. Although there was no statistically significant difference, the time to union was approximately one week shorter in the IMN group.…”
Section: Discussionmentioning
confidence: 99%